Increasing Irrigation Efficiency through Maintenance of Irrigation Network Based on Dynamic Simulation - Rahman, Mislaini; N, Bambang Pramudya; Purwanto, M Yanuar J; Solahudin, M (The University of Lampung, 2022)
Given the increasing demand for water, it is necessary to make an effort to anticipate water scarcity through increasing efficiency in an irrigation area. Increasing efficiency requires an increase in the contribution of farmers to finance the repair of irrigation canals. The purpose of this study is to formulate a financing scheme for maintenance of irrigation networks by the state and farmer participation (contribution). Research was conducted at the Cihea Irrigation Area (Cianjur Regency). The method used is system dynamics modeling by observing the parameters studied, including; asset damage, productivity, farmer contributions, public works budget and irrigation efficiency. The results of the analysis with dynamic simulations show that the best scenario to reduce damage to Cihea Irrigation assets is scenario 2 because it reduces the damage by 10.29% and increases the irrigation maintenance index by 0.05 within 10 years. Thus, it is necessary suggest to the government and farmers to increase the contribution and budget for the improvement of the Cihea Irrigation. Keywords: Asset Damage, Efficiency, Farmer's Contribution, Government Budget, Maintenance